PELATIHAN DAN DISIPLIN KERJA KARYAWAN RUMAH SAKIT PERTAMINA BINTANG AMIN BANDAR LAMPUNG - Maulana, Bima; Indriani, Wiewiek; Mufahamah, Euis; Listyaningsih, Erna (Jurnal Jejama Manajemen Malahayati, 2022)
This study aims to determine and analyze the effect of training on employee performance, to determine and analyze the effect of work discipline on performance and to determine and analyze the effect of training and work discipline on employee performance at Pertamina Bintang Amin Hospital Bandar Lampung. The approach used in this study is an associative approach. The population in this study were employees at Pertamina Bintang Amin Hospital, Bandar Lampung, amounting to 130 people. Data collection techniques in this study used interview techniques (interviews), document studies and questionnaires (questionnaires). The data analysis technique in this study uses the Classical Assumption Test, Multiple Linear Regression, t-test and F-test, and the Coefficient of Determination. Data processing in this study using the SPSS program (version 19.0). The results of this study indicate that partial training has no positive and insignificant effect on employee performance at Pertamina Bintang Amin Hospital Bandar Lampung. Work discipline partially positive and significant effect on employee performance at Pertamina Bintang Amin Hospital Bandar Lampung. Training and work discipline simultaneously have a positive effect on employee performance at Pertamina Bintang Amin Hospital in Bandar Lampung.